Micropore-rich carbon adsorbent and application thereof in separation of mixed gas of sulfur hexafluoride and nitrogen

The microporous carbon adsorbent prepared by low-temperature pre-carbonization and high-temperature activation solves the problems of low separation efficiency and high cost of SF6/N2 mixed gas in the existing technology, and achieves efficient and economical SF6 capture and separation.

CN121198237APending Publication Date: 2025-12-26YANTAI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511369398.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing adsorbents have limitations in adsorption capacity, selectivity, or high cost when separating SF6/N2 mixed gases. Furthermore, existing technologies require large investments and consume a lot of energy, making it difficult to achieve efficient and economical separation.

Method used

A two-step method of low-temperature pre-carbonization and high-temperature activation was adopted to prepare microporous carbon adsorbents. Using cellulose acetate as a precursor, the carbon skeleton was stabilized by low-temperature pre-carbonization and activated by KOH to form a regular microporous structure, thus preparing an adsorbent with high specific surface area and pore size matching SF6 molecules.

Benefits of technology

It achieves efficient separation of SF6/N2 mixed gas. The adsorbent has high adsorption capacity and selectivity for SF6, and the dynamic separation effect is significant. Moreover, the preparation process has controllable cost and is easy to scale up.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121198237A_ABST
    Figure CN121198237A_ABST
Patent Text Reader

Abstract

The invention discloses a micropore-rich carbon adsorbent and application thereof in separation of mixed gas of sulfur hexafluoride and nitrogen, and the micropore-rich carbon adsorbent is prepared by taking cellulose acetate as a precursor, performing low-temperature pre-carbonization treatment in an inert atmosphere, mixing with KOH, performing high-temperature activation in the inert atmosphere, and finally washing and drying. The carbon adsorbent prepared by a unique two-step method of low-temperature pre-carbonization and high-temperature activation has an extremely high specific surface area (1100-1700m < 2 > / g) and a pore channel structure mainly comprising micropores (the pore diameter is concentrated in 0.5-0.8 nm). The adsorbent shows ultrahigh adsorption capacity (the adsorption capacity can reach 2.83 mmol / g at the temperature of 25 DEG C and the pressure of 0.1 bar) on SF6. The carbon adsorbent disclosed by the invention is simple in preparation method, low in raw material cost and environment-friendly, and has a wide application prospect in the field of SF6 recovery and purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of porous carbon material preparation and gas adsorption and separation technology, specifically relating to a microporous carbon adsorbent with biomass derivatives as precursors, and the application of this carbon adsorbent in capturing and separating greenhouse gas SF6, especially for selectively separating SF6 from a mixture of SF6 and N2. Background Technology

[0002] SF6 is a colorless, odorless, non-toxic, and non-flammable stable gas. Due to its excellent insulating and arc-quenching properties, it is widely used in the power industry as an insulating medium for electrical equipment such as high-voltage switches, transformers, and circuit breakers. However, SF6 is also an extremely potent greenhouse gas, with a global warming potential (GWP) approximately 23,500 times that of CO2, and an atmospheric lifetime of up to 3,200 years. With increasing global concern about climate change and the implementation of relevant environmental regulations (such as the Kyoto Protocol), the recovery, regeneration, and recycling of SF6 gas used in power equipment has become an urgent need for reducing greenhouse gas emissions and achieving sustainable development.

[0003] During the operation and maintenance of power equipment, SF6 inevitably mixes with N2 and other gases in the air, forming an SF6 / N2 mixture. To achieve the recycling of SF6, it must be efficiently and economically separated from this mixture. Currently, the main industrial technologies for separating SF6 / N2 mixtures include cryogenic distillation and membrane separation. Cryogenic distillation utilizes the significant difference in boiling points between SF6 (boiling point -63.8℃) and N2 (boiling point -195.8℃) through deep freezing and distillation columns. This method is technologically mature and achieves high separation purity, but it requires substantial equipment investment and has extremely high energy consumption during the refrigeration process, resulting in high operating costs. It is typically only suitable for large-scale, centralized processing scenarios. Membrane separation utilizes the difference in permeation rates of SF6 and N2 molecules within specific polymer membranes. This method features simple equipment and lower energy consumption, but it faces a trade-off between permeability and selectivity; highly permeable membranes often have lower selectivity, and vice versa. In addition, polymer membranes may experience problems such as swelling, aging, and contamination during long-term operation, which can affect the stability of separation performance and the service life of the membrane.

[0004] In contrast, adsorption separation is considered a promising alternative technology for separating SF6 / N2 mixtures due to its advantages such as mild operating conditions, low energy consumption, simple equipment, and recyclability. The core of this technology lies in developing adsorbents with high adsorption capacity and selectivity for SF6. Currently researched adsorbents mainly include activated carbon, zeolite molecular sieves, and metal-organic frameworks (MOFs). While commercially available activated carbon is inexpensive, its wide pore size distribution and underdeveloped microporous structure result in unsatisfactory adsorption capacity and selectivity for SF6, making it difficult to meet the requirements for efficient separation. Zeolite molecular sieves have a regular pore structure, but their strong polar framework has limited affinity for the non-polar SF6 molecules, and their pore size usually does not precisely match the kinetic diameter of SF6 (0.55 nm), resulting in mediocre adsorption performance. Metal-organic frameworks (MOFs) are a new class of crystalline porous materials. Some MOFs exhibit good adsorption performance for SF6, but their synthesis process usually involves expensive organic ligands and metal salts, resulting in high preparation costs and poor hydrothermal stability, which limits their large-scale industrial application.

[0005] Therefore, developing a novel carbon adsorbent that is simple to prepare, has widely available raw materials, is inexpensive, and possesses a high specific surface area and optimized microporous structure, thereby exhibiting high adsorption capacity and high separation selectivity for SF6 / N2 mixed gases, is of great technical and economic value for promoting the application of adsorption methods in the field of SF6 recovery. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a microporous carbon adsorbent with a simple preparation process, controllable cost, high specific surface area and optimized microporous structure, and to provide a new application for the carbon adsorbent.

[0007] To achieve the above objectives, the present invention provides a microporous carbon adsorbent with a specific surface area of ​​1100–1700 m². 2 / g, total pore volume is 0.5~0.7cm³ 3 / g, and the pore size distribution is concentrated in 0.5~0.8nm.

[0008] The above-mentioned microporous carbon adsorbent was prepared by the following steps: Step 1: Low-temperature pre-carbonization Cellulose acetate is placed in an inert atmosphere and heated to 250–350°C at a heating rate of 1–5°C / min, and held at that temperature for 0.5–2 hours to obtain pre-carbonized material.

[0009] Step 2: High-temperature activation The pre-carbonized material obtained in step 1 is mixed with KOH at a mass ratio of 0.5 to 2:1. Then, in an inert atmosphere, the temperature is raised to 700 to 850°C at a heating rate of 3 to 10°C / min and held for 2 to 4 hours to obtain the activated product.

[0010] Step 3: Post-processing The activated product obtained in step 2 was washed repeatedly with deionized water to remove residual potassium salts and other inorganic impurities until the pH of the washing solution was neutral. Then it was dried to obtain a microporous carbon adsorbent.

[0011] Furthermore, in step 1 above, it is preferable to heat the temperature to 300°C at a heating rate of 1-2°C / min and hold it at that temperature for 1 hour.

[0012] Furthermore, in step 1 above, the inert atmosphere is argon or nitrogen, preferably with a gas flow rate of 50-200 mL / min.

[0013] Furthermore, in step 2 above, the mass ratio of the pre-carbonized material to KOH is preferably 1:1.

[0014] Furthermore, in step 2 above, it is preferable to heat the temperature to 750-800°C at a heating rate of 5-8°C / min and hold it at that temperature for 3 hours.

[0015] This invention also provides the application of the aforementioned microporous carbon adsorbent in the efficient separation of SF6 / N2 mixed gases, aiming to solve the problems of limited adsorption capacity, insufficient selectivity, or high cost of existing adsorbents in SF6 / N2 separation. The unique pore structure of the microporous carbon adsorbent provided by this invention is highly matched to the kinetic diameter of SF6 molecules (approximately 0.55 nm), thereby generating a strong adsorption effect. It exhibits a much stronger affinity and preferential adsorption capacity for SF6 molecules than for N2 molecules. When the SF6 / N2 mixed gas passes through an adsorption bed filled with the microporous carbon adsorbent of this invention, the larger SF6 molecules with higher polarizability are preferentially captured in the micropores of the adsorbent, while the smaller N2 molecules with weaker interactions are almost not adsorbed and pass directly through the adsorption bed, thus achieving efficient separation of the two components.

[0016] This invention utilizes a two-step heat treatment process to transform inexpensive cellulose acetate into a microporous carbon material with a specific pore structure, and successfully applies it to the efficient separation of SF6 / N2. The first step is low-temperature pre-carbonization. A relatively low temperature of 250–350°C is chosen to remove hydroxyl and acetyl groups without damaging the basic chain structure of the cellulose macromolecules, thus initially forming a stable carbon skeleton with low cross-linking degree. This process avoids the structural collapse and low yield problems that may occur with direct activation at high temperatures, laying the foundation for subsequent high-temperature activation and pore formation. The second step is high-temperature activation with KOH. KOH, as a strong chemical activator, reacts with the pre-carbonized material at a high temperature of 700–850°C. The reaction mechanism is complex, but it is generally believed to include the dehydration of KOH and the redox reaction with carbon to produce metallic potassium, K2CO3, and H2 (e.g., C + 6KOH → 2K + 3H2 + 2K2CO3). In this process, potassium vapor can embed itself between the carbon layers, acting as a template and support, effectively expanding the carbon layers and forming abundant micropores. After the reaction, potassium species are removed by washing, leaving pores that constitute the rich microporous network of the material. The carbon adsorbent obtained in this invention has micropores of 0.5–0.8 nm, which are considered ideal “traps” for capturing SF6 (kinetic diameter 0.55 nm). When the SF6 / N2 mixed gas flows through the adsorbent, due to van der Waals forces, SF6 molecules, which have higher polarizability and larger molecular size, preferentially enter and fill these micropores, while N2 molecules (kinetic diameter 0.364 nm) have much weaker interactions with the pore walls and are at a disadvantage in competitive adsorption. Therefore, most N2 molecules pass through with the gas flow, thus achieving efficient separation.

[0017] Compared with the prior art, the present invention has the following significant advantages: 1. The two-step method of “low-temperature pre-carbonization + high-temperature activation” adopted in this invention uses cellulose acetate as a precursor, which is widely available and inexpensive. The low-temperature pre-carbonization step stabilizes the carbon skeleton, improves the yield, and is conducive to the subsequent formation of regular micropores. Combined with a simple KOH activation process, the entire preparation process is cost-controllable and easy to scale up for production.

[0018] 2. The carbon adsorbent prepared by this invention has an extremely high specific surface area (up to 1700 m²). 2 The pore structure (with a diameter of 0.5–0.8 nm) and the precisely controlled microporous structure, which is highly matched to the molecular size of SF6, provide a large number of advantageous adsorption sites and form the structural basis for achieving high-performance adsorption separation.

[0019] 3. The adsorbent of this invention exhibits an unprecedentedly high adsorption capacity for SF6. Under the conditions of 25°C and 0.1 bar (simulating the partial pressure of SF6 in a mixed gas), the adsorption capacity of pure SF6 is as high as 2.83 mmol / g, which is significantly better than all carbon-based adsorbents reported in the literature.

[0020] 4. The adsorbent of this invention has a much stronger adsorption capacity for SF6 than for N2. Dynamic breakthrough experiments have confirmed that SF6 can be effectively captured by the adsorption column for up to 60 minutes, while N2 passes through rapidly, thus achieving efficient separation of SF6 / N2 mixed gas. Attached Figure Description

[0021] Figure 1 The images show the nitrogen adsorption-desorption isotherm of the microporous carbon adsorbent prepared in Example 1 at 77 K and the pore size distribution calculated by nonlocal density functional theory (NLDFT).

[0022] Figure 2 This is the adsorption isotherm diagram of pure components SF6 and N2 at 25°C for the microporous carbon adsorbent prepared in Example 1.

[0023] Figure 3 The graph shows the dynamic breakthrough experiment curve of the microporous carbon adsorbent prepared in Example 1 against the SF6 / N2 (10:90, v / v) mixed gas at 25°C and 1 bar total pressure. Detailed Implementation

[0024] The technical solution of the present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions or modifications made based on the content of this invention should be included within the scope of protection of this invention. Example 1

[0025] Step 1: Low-temperature pre-carbonization 4.0 g of commercially available cellulose acetate powder was accurately weighed and placed in a ceramic boat. The boat was then placed in a tube furnace and heated from room temperature to 300 °C at a heating rate of 1 °C / min under an argon atmosphere (flow rate 100 mL / min), and held at 300 °C for 1 hour. Afterward, it was allowed to cool naturally to room temperature, yielding a black pre-carbonized material, denoted as CA-300. The yield was approximately 36%.

[0026] Step 2: High-temperature activation The pre-carbonized material obtained in step 1 was thoroughly ground and mixed with an equal mass of KOH powder in an agate mortar. The mixture was then placed in a porcelain boat and placed in a tube furnace. Under an argon atmosphere (flow rate 100 mL / min), the temperature was increased from room temperature to 750°C at a rate of 5°C / min, and activated at 750°C for 3 hours. After activation, the mixture was allowed to cool naturally to room temperature to obtain the activated product.

[0027] Step 3: Post-processing The activated product obtained in step 2 was repeatedly filtered and washed with deionized water to remove residual potassium salts and other inorganic impurities until the pH of the washing solution was neutral. The resulting filter cake was dried in a vacuum drying oven at 110°C for 12 hours to obtain microporous carbon adsorbent powder, denoted as CAK-750.

[0028] The prepared CAK-750 sample was subjected to N2 adsorption-desorption tests at 77 K using a 3Flex physical adsorption instrument from Micron Instruments, Inc. The results are as follows: Figure 1 As shown, the N2 adsorption-desorption isotherm of CAK-750 exhibits typical type I isotherm characteristics, indicating its abundant microporous structure. In the low relative pressure region (P / P... 0 When the adsorption rate was < 0.1, the adsorption capacity increased sharply, followed by a gradual plateau, confirming the dominance of micropores. Analysis of the adsorption data using a nonlocal density functional theory (NLDFT) model revealed a specific surface area as high as 1518 m². 2 / g, total pore volume is 0.62cm³ 3 / g. Pore size distribution ( Figure 1 (Illustration) The results show that the pore size distribution of CAK-750 is very narrow, mainly concentrated between 0.5 and 0.8 nm, with a peak pore size of about 0.65 nm. Example 2

[0029] In step 2 of this embodiment, the temperature was increased from room temperature to 700°C at a heating rate of 5°C / min, and then activated at 700°C for 3 hours. Other steps were the same as in Example 1, yielding a microporous carbon adsorbent powder, denoted as CAK-700. Testing showed that the total specific surface area of ​​CAK-700 was 1403 m². 2 / g, total pore volume is 0.62cm³ 3 / g, the pore size distribution is also mainly micropores, but the pore volume is lower than that of CAK-750, indicating that the activation degree at 700℃ is not sufficient. Example 3

[0030] In step 2 of this embodiment, the temperature was increased from room temperature to 850°C at a heating rate of 5°C / min, and then activated at 850°C for 3 hours. Other steps were the same as in Example 1, yielding a microporous carbon adsorbent powder, denoted as CAK-850. Testing showed that the total specific surface area of ​​CAK-850 was 1491 m². 2 / g, total pore volume is 0.69 cm³ 3 / g, the pore size distribution shows that in addition to the main peak at 0.5-0.8 nm, a small number of pores begin to appear at 1-2 nm, indicating that excessively high activation temperature may lead to the expansion or collapse of some micropores. Example 4

[0031] Application of the carbon adsorbent CAK-750 prepared in Example 1 for adsorption and separation of SF6 / N2 mixed gas 1. Pure component gas adsorption isotherm test Using a physical adsorption apparatus, the adsorption-desorption isotherms of high-purity SF6 and high-purity N2 were measured in the pressure range of 0–100 kPa under a constant temperature of 25 °C. Before testing, the samples were activated under vacuum at 200 °C for at least 4 hours.

[0032] Test results are as follows Figure 2 As shown, CAK-750 adsorbs significantly more SF6 than N2 across the entire pressure range. At 0.1 bar (simulating the partial pressure of SF6 in a 10:90 SF6 / N2 mixture), the adsorption capacity of SF6 reaches as high as 2.83 mmol / g, demonstrating extremely strong SF6 capture capability at low partial pressures.

[0033] 2. Dynamic penetration experiment To simulate the actual separation process, a dynamic breakthrough experimental setup was constructed. 0.5 g of CAK-750 was packed into a 7 mm inner diameter stainless steel adsorption column and placed in a constant temperature water bath at 25 °C. Before the experiment, the adsorbent was activated by purging with high-purity He at 100 °C for 0.5 h. At the start of the experiment, a standard gas mixture of SF6 / N2 (10:90, v / v) at a total flow rate of 5 mL / min was introduced into the adsorption column. The gas composition at the column outlet was analyzed online in real time by a gas chromatograph (GC) equipped with a thermal conductivity detector (TCD).

[0034] Experimental results are as follows Figure 3As shown in the figure, the horizontal axis represents time (min), and the vertical axis represents the ratio of the concentration of SF6 (C) in the outlet gas to the concentration (C0) in the inlet gas (C / C0). The figure shows that for a considerable period after the experiment began, SF6 was undetectable in the outlet gas (C / C0 ≈ 0), indicating that SF6 was completely captured by the adsorbent. N2, due to its extremely weak adsorption, penetrated the adsorption column at 0 min. The breakthrough time of SF6 (defined as the moment when C / C0 = 0.05) was approximately 60 min. This result directly demonstrates that the adsorbent of this invention can effectively separate SF6 and N2 under dynamic flow conditions.

Claims

1. A microporous carbon-rich adsorbent, characterized by: The specific surface area of the microporous carbon adsorbent is 1100-1700 m 2 / g, the total pore volume is 0.5-0.7 cm 3 / g, and the pore size distribution is concentrated in 0.5-0.8 nm; The microporous-rich carbon adsorbent is prepared by the following steps: Step 1: low-temperature pre-carbonization The cellulose acetate is heated to 250-350℃ at a heating rate of 1-5℃ / min in an inert atmosphere and kept for 0.5-2h to obtain a pre-carbonized material; Step 2: high-temperature activation The pre-carbonized material obtained in Step 1 is mixed with KOH at a mass ratio of 0.5-2:1, and then heated to 700-850℃ at a heating rate of 3-10℃ / min in an inert atmosphere and kept for 2-4h to obtain an activated product; Step 3: post-treatment The activated product obtained in Step 2 is washed with deionized water until neutral, and then dried to obtain the microporous-rich carbon adsorbent.

2. The microporous carbon-rich adsorbent of claim 1, wherein: In Step 1, the heating rate is 1-2℃ / min to 300℃ and kept for 1h.

3. The microporous carbon-rich adsorbent of claim 1 or 2, wherein: In Step 1, the inert atmosphere is argon or nitrogen, and the gas flow rate is 50-200mL / min.

4. The microporous carbon-rich adsorbent of claim 1, wherein: In Step 2, the mass ratio of the pre-carbonized material to KOH is 1:

1.

5. The microporous carbon-rich adsorbent of claim 1 or 4, wherein, In Step 2, the heating rate is 5-8℃ / min to 750-800℃ and kept for 3h.

6. Use of the microporous-rich carbon adsorbent of claim 1 in separating sulfur hexafluoride from a nitrogen gas mixture.

Citation Information

Cited By

  • Microporous-mesoporous graded carbon molecular sieve for capturing low-concentration SF6 as well as preparation and application of microporous-mesoporous graded carbon molecular sieve

    CN121778729A

  • Microporous-mesoporous hierarchical carbon molecular sieves with low concentration SF6 capture, their preparation and application

    CN121778729B